ANALISIS DAMPAK LALU LINTAS PADA SIMPANG TAK BERSINYAL DI SIMPANG BULUSAN - GONDANG TEMBALANG KOTA SEMARANG - Mahbub, Jamal; Wahjoedi, Wahjoedi; Buana, Lalu Yahya Surya; Nurhadi, Imam; Risman, Risman (Politeknik Negeri Semarang, 2024)
Vehicles that park on the road cause traffic jams and obstruct traffic flow as well as reducing the level of road service. The ability of a road to provide good and maximum traffic services is closely related to the capacity of the road section. Apart from road capacity, the performance of a road is also closely related to traffic performance. This method is used to analyze the condition of road sections. In the results of road performance analysis by calculating the level of road service, the V/C Ratio value is obtained which will indicate the level of service. Research in a traffic flow movement on a highway there are three main variables used to describe the characteristics of traffic flow , namely speed, volume and density. On the Jl. Sipodang has a capacity of 1638,291 pcu/hour and the average volume on this road is 741.79 pcu/hour, and has a degree of saturation of 0.45 where this figure is in service level C with the characteristics of stable flow, but speed and vehicle motion is controlled, the driver is limited in choosing speed. On the Jl. Gondang Raya has a capacity of 1486,285 pcu/hour and the average volume on this road is 1535.2 pcu/hour, and has a degree of saturation of 1.03 where this figure is at service level E with characteristics of obstructed flow, low speed, volume above capacity, traffic jams often occur for quite a long time. On the Jl. Soeparto from the west has a capacity of 2925.52 pcu/hour and the average volume on this road is 1697.09 pcu/hour, and has a degree of saturation of 0.58 where this figure is at service level C with the characteristics of stable flow, but the speed and motion of the vehicle are controlled, the driver is limited in choosing the speed. On the Jl. Soeparto from the west has a capacity of 2925.52 pcu/hour and the average volume on this road is 1506,171 pcu/hour, and has a degree of saturation of 0.51 where this figure is at service level C with characteristics of stable flow. , but the speed and motion of the vehicle are controlled, the driver is limited in choosing the speed.